EDUCATIONAL SYSTEM AND NEOLIBERAL EDUCATIONAL POLICY - Georgios Pappas (Borys Grinchenko Kyiv Metropolitan University, 2020)
The aim of this paper is to track, record and highlight the implications of the application of market principles in education. The supporters of the above mentioned view, consider that the pedagogical science is allowed to provoke to its clientele neither «spleepiness» nor fleeing. On the contrary, those who oppose the application of the principles of the market in education, consider that by the logic of the market, schools and universities are turned into businesses and students into a two-category workforce, depending on their degrees and financial capacity. Through the examination of labour market's implementation in education, the aims that are served and the social inequalities which are established, become apparent. Moreover, in this paper, an effort is attempted to highlight the true nature of education and the role that all participants in the educational system should play.